Doctor-Patient Communication for Adherence to Hypertension Treatment in Nepal - Sah, Ram Kishor; Khanal, Hari Har; Shrestha, Deepak Sundar; Paudel, Bishnu Dutta; Gautam, Roshani; Straus, Andrea M; Love, Richard R. (Nepalese Medical Journal, 2020)
Effective doctor-patient communication is key to addressing the signifi cant issue of nonadherence to hypertension treatment in Nepal. Common clinical messages about hypertension are evaluated utilizing the framework of the Common-Sense Model of Self-Regulation for their role in shaping the patient models that underlie nonadherent behavior. Clinical communications and practices are recommended: to respectfully elicit and address patient reliance on self-identifi ed symptoms; to accompany warnings of hypertension’s serious consequences with specifi c individual action-plans for durable effects; to emphasize the necessity of long-term continuous treatment without creating fears of dependence and withdrawal effects or burdensome monitoring and counseling; to inform of side-effects while presenting medication as nontoxic and necessary for the body’s maintenance of a healthy balance. By acknowledging the patient as an active agent engaged in self-regulation and by employing culturally consonant concepts (often Ayurvedic), we can encourage accurate patient illness and treatment representations that guide medication adherence.